THE EFFECT OF PROFIT MANAGEMENT AND CORPORATE GOVERNANCE TOWARDS FINANCIAL STATEMENT FRAUD - Safira Novriana Yasmin Safira Novriana Yasmin; Rieka Ramadhaniyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The purpose of this study was to obtain empirical evidence regarding the effect of Profit Management and Corporate Governance towards Financial Statement Fraud of registered transportation companies on the Indonesia Stock Exchange in 2016-2018. The population of this study was the registered transportation companies on the Indonesia Stock Exchange (BEI) in 2016-2018. The technique of selecting samples was purposive sampling. Therefore, the sample was 22 transportation companies. The analytical method used logistic regression method. The results of this study proved that profit management, institutional ownership, managerial ownership, size of the commissioner's board, independent commissioners, and Big-4 Accounting Firms did not affect on financial statement fraud. Furthermore, the Audit Committee affected on financial report fraud.